1999
DOI: 10.1001/archinte.159.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Serum β-Hydroxybutyrate Measurement in Patients With Uncontrolled Diabetes Mellitus

Abstract: The correlations between serum beta-OHB and carbon dioxide levels and the anion gap were close, but not sufficiently so for the beta-OHB measurements to be routinely useful alone to assess the severity of the ketoacidosis. Full laboratory assessment of the severity and characteristics of ketoacidosis also requires knowledge of serum carbon dioxide level, anion gap, often blood pH, and ideally serum acetoacetate and lactate concentrations as well as serum beta-OHB concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…We agree with Fulop et al [27] in their analysis of whether routinely measuring b-OHB concentration might help judge the severity of suspected diabetic ketoacidosis in that b-OHB measurements alone are not sufficient for the laboratory assessment of the severity and characteristics of ketoacidosis. Knowledge of other biochemical markers is also required.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We agree with Fulop et al [27] in their analysis of whether routinely measuring b-OHB concentration might help judge the severity of suspected diabetic ketoacidosis in that b-OHB measurements alone are not sufficient for the laboratory assessment of the severity and characteristics of ketoacidosis. Knowledge of other biochemical markers is also required.…”
Section: Discussionsupporting
confidence: 88%
“…b-OHB serum concentrations might provide more information about the severity of ketoacidosis [26,27], whether it is related to diabetes [28], alcohol [29] or starvation [30]. The clinical symptoms of ketoacidosis in diabetes mellitus are very similar to those of alcoholic ketoacidosis and a differential diagnosis is necessary [31].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, such a conclusion must be arrived at on theoretical grounds. Fulop et al (21) compared ␤OHB to both serum CO 2 content and anion gap in 64 DKA encounters and concluded that the correlations were too weak for ␤OHB to be useful to assess the severity of ketoacidosis. This conclusion is based on the assumption that HCO 3 is the "gold standard" for diagnosing DKA, however.…”
Section: Research Design and Methods -We Retrieved Electronic Medicalmentioning
confidence: 99%
“…The syndrome of alcoholic ketoacidosis (AKA) is uncommon in patients with acute ethanol intoxication, being found in Ͻ10% of patients (112)(113)(114). It is most frequent in patients who have long-term ethanol intake and liver disease and develop the syndrome after a period of binge drinking (39,112) and is associated with reduced food intake and episodes of vomiting; the latter might explain the concurrence of metabolic alkalosis noted in some patients (39,112,115,116).…”
Section: Epidemiologymentioning
confidence: 99%
“…Excess production of acetoacetic acid and ␤-hydroxybutyric acid underlies the metabolic acidosis, with increased NADH favoring production of ␤-hydroxybutyrate compared with acetoacetate (115), the ratio of these ketones rising from the normal value of 3:1 to more than 9:1 (112)(113)(114)(115). The increased NADH also favors increased lactic acid production; therefore, concomitant lactic acidosis even in the absence of impaired tissue perfusion is not uncommon (39,112,115).…”
Section: Pathophysiologymentioning
confidence: 99%